Impact of COVID-19 Pandemic on Life-Space Mobility of Older Adults Living in Brazil: REMOBILIZE Study - Perracini, Monica R.; de Amorim, Juleimar Soares Coelho; Lima, Camila Astolphi; da Silva, Alexandre; Trombini-Souza, Francis; Pereira, Daniele Sirineu; Pelicioni, Paulo Henrique Silva; Duim, Etiene; Batista, Patricia Parreira; dos Santos, Renato Barbosa; de Lima, Maria do Carmo Correia, The REMOBILIZE Research Network (CANSORT-SCI) (Frontiers in Public Health, 2021)
Background: The COVID-19 pandemic hit Brazil in a scenario of substantial socioeconomic and health inequalities. It is unknown the immediate impact of social restriction recommendations (i.e., lockdown, stay-at-home) on the life-space mobility of older people. Objective: To investigate the immediate impact of the COVID-19 pandemic on life-space mobility of community-dwelling Brazilian older adults and examine the social determinants of health associated with a change in life-space mobility. Design: Baseline data from a prospective cohort study (REMOBILIZE Study). Setting: Community. Subject: A convenience snowball sample of participants aged 60 and older (n=1,482) living in 22 states in Brazil. Methods: We conducted an online and phone survey using an adapted version of the Life-Space Assessment (LSA). Linear regression models were used to investigate social determinants of health on the change in LSA score. Results: Regardless of their gender and social determinants of health, participants showed a significant reduction in life-space mobility since the COVID-19 pandemic outbreak. Life-space mobility reduction was higher among black individuals, living alone and aged between 70 and 79. Other variables associated with a change in life-space mobility, to a lesser extent, were sex, education, and income. Conclusion: Social restriction measures due to pandemic caused a substantial reduction in older adults’ life-space mobility in Brazil. Social inequalities strongly affected vulnerable groups. Concerted actions should be put in place to overcome the deterioration in life-pace mobility amongst these groups. Failure in minimizing health inequalities amplified by the pandemic may jeopardize the desired achievements of the Decade of Healthy Ageing.